Hubungan antara Pengetahuan dan Sikap Keluarga dengan Kemampuan dalam Pelaksanaan Oral Hygiene di Ruang Musdalifah RSI Siti Khadijah Palembang - Lenny Astuti; Ahmad Khoiri (Jurnal Kesehatan, 2017)
Patients with consciousness disorder may experience physical mobility and swallowing food disorder through the mouth so it can be one cause of inflammation of the mucous membranes of the mouth. Oral hygiene in oral and dental health is very important. The aim of this study was to determine the relationship between knowledge, family attitudes, and ability in oral hygiene implementation at musdalifah room Siti Khadijah Islamic Hospital Palembang in 2017. This study used quantitative with the cross sectional design. The population of this study was all family of patients that treated at Musdalifah Room Siti Khadijah Islamic Hospital Palembang in 2017. The number of samples was 91 respondents. Analysis the data used by univariate and bivariate. The result is Most of them have good knowledge were 51 respondents (56.0%), most have positive attitude were 49 respondents (53.8%) and most have good oral hygiene implementation ability were 58 respondents (63,7%). Based on the analysis using chi-square test, there was a correlation between knowledge with ability in oral hygiene implementation (ρ = 0,027) and there was a relationship of attitude with ability in oral hygiene implementation (ρ = 0,016). Finally, it is expected that this study could be a reference to improve the quality of professionalism in providing services to critical patients to be able to improve the ability of oral hygiene implementation.